The “construction” of the Greek landscape in the Hellenistic era - Iliopoulou Filio (Projets de Paysage)
In recognition of the importance of landscape as a crucial factor in the birth and evolution of civilizations, the current on-going doctorate thesis examines the way the Greek landscape was constructed - if at all - in the Hellenistic era, claiming that its design was based on certain architectural principles which reflect the political and social values of that historical period. The doctorate thesis of Constantinos A. Doxiadis, “Architectural Space in Ancient Greece”, will be used as the basis upon which the current research will develop its own arguments related to the ways the particular characteristics of the ancient Greek landscape dictated a pre-defined course through the built and unbuilt environment, which was perceived as an inseparable unity. The theoretical analysis of the principles by which the Greek landscape was “constructed” in the Hellenistic era will be informed constantly throughout this process by the findings of the most thoroughly excavated town of that period, the ancient Messene.